A Versatile Iron–Tannin‐Framework Ink Coating Strategy to Fabricate Biomass‐Derived Iron Carbide/Fe‐N‐Carbon Catalysts for Efficient Oxygen Reduction. (11th December 2015) - Wei, Jing; Liang, Yan; Hu, Yaoxin; Kong, Biao; Simon, George P.; Zhang, Jin; Jiang, San Ping; Wang, Huanting
Abstract: The conversion of biomass into valuable carbon composites as efficient non‐precious metal oxygen‐reduction electrocatalysts is attractive for the development of commercially viable polymer electrolyte membrane fuel‐cell technology. Herein, a versatile iron–tannin‐framework ink coating strategy is developed to fabricate cellulose‐derived Fe3 C/Fe‐N‐C catalysts using commercial filter paper, tissue, or cotton as a carbon source, an iron–tannin framework as an iron source, and dicyandiamide as a nitrogen source. The oxygen reduction performance of the resultant Fe3 C/Fe‐N‐C catalysts shows a high onset potential (i.e. 0.98 V vs the reversible hydrogen electrode (RHE)), and large kinetic current density normalized to both geometric electrode area and mass of catalysts (6.4 mA cm −2 and 32 mA mg −1 at 0.80 V vs RHE) in alkaline condition. This method can even be used to prepare efficient catalysts using waste carbon sources, such as used polyurethane foam.